Research on intelligent path planning method based on YOLOv4 semantic perception - Yunhe, X. (Инноватика-2025 : сборник материалов XXI Международной школы-конференции студентов, аспирантов и молодых ученых, 28-30 апреля 2025 г., г. Томск, Россия)
A proposed real-time path planning framework uses transfer learning to map feature responses of the YOLOv4 object detection model into a repulsive field for fast obstacle avoidance in dynamic environments.